Clinical Characteristics of Covid-19 in Libya: Case Series - Ehmeid Khalifa; Ehab Omrani; Mohamed Bashagha (AlQalam Journal of Medical and Applied Sciences, 2021)
Background and objectives: In the face of emerging and rapidly spread of coronavirus disease 2019 (Covid-19) in Libya, it is important to fully understand the spectrum of initial symptoms of the infected patients in order to identify new cases as early as possible. The current study describes the initial observation of clinical characteristics of COVID-19 among Libyan patients. Early detection and identification of suspected cases should lead to systematic screening for the disease and could be helpful to ensure immediate isolation until a definite diagnosis is made. Methods: This case series study evaluated 325 confirmed COVID-19 infected patients who made a contact with Covid-19 Emergency Response Centre (CERC) in the period from October 20, 2020, to November 30, 2020. All cases were diagnosed by reverse-transcriptase polymerase-chain-reaction test (RT-PCR). Data were extracted from Zendesk Software in CERC and SPSS was used for data analysis. Results: In our study, the mean (SD) age of infected patients was 57.6 (19.1%) years, with 59% were ≥ 50 years and 194 (60%) were male. Our study found that 215 (66%) of our patients had shortness of breath. Shortness of breath was identified as the commonest clinical feature among the infected patients in this study. However, we found that 179 (55%) of patients had fever, which was similar to many studies conducted previously on the COVID-19 patients. In our study, about 165 (51%) of patients had cough and 78 (24%) of our patients had anosmia and ageusia. Conclusion: This case series demonstrated that the characteristics of Libyan COVID-19 patients were generally similar to what was published in other literatures, although we reported more respiratory symptoms at presentation such as shortness of breath (66%) and generalized fatigability (61%) as the commonest features in the study.